Bridging the Curriculum-Industry Gap in Semiconductor Talent Development: Micromodule Initiatives in Unimas - Nordiana, Rajaee; Rohana, Sapawi; Asrani, Lit; Shamsiah, Suhaili; Dayang Nur Salmi Dharmiza, Awang Salleh; Lee Chin, Kho; Annie, Joseph (2025)
The academia-industry gap has always been a prominent recurring issue in engineering education. The disconnection between the knowledge imparted in academic settings and the practical requirements of the job market often causes a mismatch in career paths and critical talent shortages in industries. Therefore, adjustments to address this gap are crucial to ensure the sustainability of our economy and to promote more collaboration between the academia and industry. In this paper we discuss micromodules to bridge the gap between the academic curriculum in the Department of Electrical and Electronics Engineering, Faculty of Engineering UNIMAS and the local semiconductor industry needs. Although the micromodules are only at the beginning phase and much more improvement is needed, this step aims to start off active collaboration between the academia and the semiconductor industry.